GAMBARAN TINGKAT PENGETAHUAN SISWA TENTANG PERTOLONGAN PERTAMA PADA KECELAKAAN DI KELAS XI SMA ST. PETRUS MEDAN TAHUN 2024 - Merry Prina Br Regar; Jagentar Parlindungan Pane; Murni Sari Dewi Manullang (Poltekkes Kemenkes Medan, 2024)
First Aid for Accidents (P3K) is the action of providing first aid to accident victims before taking them to a hospital, clinic or other health institution so that they can obtain further medical assistance from a doctor or paramedic. Accidents can occur in any group, one of which is school students. Based on the results of interviews, the majority said that students who faint will receive first aid at the UKS (school health unit). Accidents that occur at school are very diverse, such as children slipping which causes lacerations or bruises, food poisoning, choking on food, fainting and so on. The aim of this research is to determine the description of students' knowledge about first aid in accidents in class The sample is total sampling. This research instrument uses a first aid knowledge questionnaire sheet which has been tested as valid (Pearson product moment 0.361) and reliable (Cronbach Alpha 0.985). The results of this research showed that the description of the knowledge who have good knowledge about First Aid are 97 respondents (91.5%) and 9 respondents (8.5%) have sufficient knowledge. The solution that can be implemented so that all students can have good knowledge is to provide health education so that they can increase students' knowledge and skills in providing first aid in accidents.